Attitude of Students Towards the Study of Physics: A Case of Tamale College of Education, Ghana. - Moses Kojo Asare Mabee; Tahiru Zingani Haruna; Abdallah Salifu (Noyam Journals, 2021)
The study examined the attitude of third-year science and mathematics students towards the study of Physics in the Tamale College of Education, Ghana. A case study involving a sample of one hundred and thirty-three students was adopted for the study. Using a structured questionnaire, data was collected from the selected sample. The Likert rating scale was adopted to indicate the extent of agreement or disagreement. General findings from the study indicated that the majority of the respondents had a negative perception towards the study of Physics. The research recommended that preferably only students who offered Elective Physics at the Senior High School level should be admitted to study Physics at the College level as this would facilitate the smooth teaching and learning of the subject. It was also suggested that Physics tutors should use innovative strategies to make the teaching and learning of the subject interesting and attractive.